Pemetaan Lahan Pertanian Berbasis Data Spasial Menggunakan Aplikasi QGIS di Desa Mojorembun Kecamatan Rejoso - Syukira, Nikma Syukira; Utomo, Sabrina Salsabila; Rakhmayanti, Dyah; Herdyan, Rafi Dhianaufal; Rohmat, Xepy Abdul; Rifki, Muhamad Fahri Nur; Saputra, Angga; Fatiyah, Salsabila; Liyantono, Liyantono (Jurnal Pusat Inovasi Masyarakat, 2024)
The high need for fast and accurate information in the data collection of agricultural land currently requires a digital mapping system. Digital mapping that utilises advanced technologies, such as Geographic Information Systems (GIS) and satellite imagery, is capable of producing detailed and accurate data on the condition of agricultural land. With its ability to provide real-time updates and integrate various data thoroughly, digital mapping is becoming an indispensable tool to fulfil the need for fast and precise information. Quantum Geographic Information System (QGIS) is an open-source GIS software that uses referenced spatial data or geographic coordinates presented in graphical form through maps. QGIS can be applied to mapping shallot farmland in Mojorembun Village. The purpose of using QGIS is to facilitate the community in accessing information and processing data related to ownership, area, and types of agricultural commodities in the village. The QGIS application provides various features, such as a land map that contains information about the location, area, and land ownership data. The results of this mapping are expected to be utilised by the community to obtain more complete information about agricultural land in Mojorembun Village.